Agricultural and Finance Intervention Increased Dietary Intake and Weight of Children Living in HIV-Affected Households in Western Kenya. Issue 2 (11th January 2020) - Butler, Lisa M; Bhandari, Shiva; Otieno, Phelgona; Weiser, Sheri D; Cohen, Craig R; Frongillo, Edward A
ABSTRACT: We tested whether a multisectoral household agricultural and finance intervention increased the dietary intake and improved the nutritional status of HIV-affected children. Two hospitals in rural Kenya were randomly assigned to be either the intervention or the control arm. The intervention comprised a human-powered water pump, microfinance loan for farm commodities, and training in sustainable farming practices and financial management. In each arm, 100 children (0–59 mo of age) were enrolled from households with HIV-infected adults 18–49 y old. Children were assessed beginning in April 2012 and every 3 mo for 1 y for dietary intake and anthropometry. Children in the intervention arm had a larger increase in weight (β: 0.025 kg/mo, P  = 0.030), overall frequency of food consumption (β: 0.610 times · wk –1 · mo –1, P  = 0.048), and intakes of staples (β: 0.222, P  = 0.024), fruits and vegetables (β: 0.425, P  = 0.005), meat (β: 0.074, P  < 0.001), and fat (β: 0.057, P  = 0.041). Livelihood interventions have potential to improve the nutrition of HIV-affected children. This trial was registered at clinicaltrials.gov as NCT01548599.